ARTHASHASTRA V/S GRAHASHASTRA- A CRITICAL ANALYSIS OF GOLD MONETISATION SCHEME (GMS) IN INDIA - Patni, Ity; Choubey, Somya (International Journal of Research -GRANTHAALAYAH, 2016)
Indian people treasure investment in Gold. The quantum of perceived value weighs more as emotional quotient is higher for this yellow metal. Families in India think that ‘gold brings good fortune’. This inclination can be observed with the supporting fact that India has outshined itself as the largest gold consumer with 703 tons of gold jewelry in the year 2015. The summative demand of gold jewelry and investment has risen by 6% through which the demand has surged to 890 tons in this year (Shawn, 2016). Phenomenon for investment in gold in India and China is inelastic, despite of price fluctuations, populace continues gaze at gold.